The Regional Inequalities in the European Union and the Countries of Community Cohesion (Portugal,Spain,Ireland and Greece) - Trifon Kostopoulos (European Regional Science Association (ERSA), 2001)
An attempt will be made, in this article,to analyze the regional inequalities within the European Union emphasizing in the countries of Communty Cohesion and the relationship between North and South.The estimation of regional policy in thi level will be made with the following variables:the deviations from the average community Gross Domestic Product GDP) the annual growth rates og GDP and the level of Unemployment. During the process of European integration it has been observed changes in the classification of the cohesion countries within the European Union.It will be an effort to estimate if these changes have been caused from the policies of the European Union or from the national policies of the member states. The analysis will be made in comparative terms among the supernational policies of the EU and the national policies of countries of community cohesion.
Keywords: 330